(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
The article explores the multiplicity of contemporary Nepali paintings in terms of Nepali tradition and contemporary experiments. Globalization enhanced the creative flow of ideas and events in the domain of art. Th condition of cultural encounter and ambivalence appear in the context of Nepali art as the effects of globalization. We can trace the native images, symbols, icons and forms interacting with western techniques in the artworks. The paintings depict the representation of cultural self and cultural other. Using the techniques of irony and parody, the visual texts respond and accommodate the alien forms. We can see how heterogeneous images, genres and cultures are criss-crossed within the paintings in the context of pervasive semiotic flow. The artworks present the dialogue of vision and textuality, tradition and modernity along with continuity and change making the work open-ended and plural having multiple significances.